Proceedings of the 2020 DigitalFUTURES 2021
DOI: 10.1007/978-981-33-4400-6_17
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on the Formation of the General Layouts on the Northern Neighborhood Community Based on GauGAN Diversity Output Generator

Abstract: Recently, the mainstream gradually has become replacing neighborhood-style communities with high-density residences. The original pleasant scale and enclosed residential spaces have been broken, and the traditional neighborhood relations are going away. This research uses machine learning to train the model to generate a new plan, which is used in today’s residential design. First, in order to obtain a better generation effect, this study extracts the transcendental information of the neighborhood community in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In terms of research on diversity generation of layouts. Pan [6] obtained the results of diverse generation by using GauGAN model to generate the layout of the neighborhood community in north of China. This study showed us the possibility of deep learning for diverse layout output, which affected the output results by changing the images of the input.…”
Section: Related Work In the Field Of Architectural Layoutmentioning
confidence: 99%
“…In terms of research on diversity generation of layouts. Pan [6] obtained the results of diverse generation by using GauGAN model to generate the layout of the neighborhood community in north of China. This study showed us the possibility of deep learning for diverse layout output, which affected the output results by changing the images of the input.…”
Section: Related Work In the Field Of Architectural Layoutmentioning
confidence: 99%
“…Pasquero and Poletto [11] used cycleGAN to explore "non-human" urban forms by transferring biomorphic styles to the urban fabric. Pan et al [10] trained a large sample of northern neighborhoods to generate diverse layouts within a plot [10]. Fedorova [2] used the model trained by five existing urban environments to observe the possibility of style transfer between different cities, and presented quantitative and qualitative evaluations of the results (Table 2).…”
Section: Applications Of Deep Learning In Urban Designmentioning
confidence: 99%
“…GauGAN is an image translation algorithm published by Nvidia Lab in 2019 to achieve multi-modal synthesis (Park et al, 2019). Compared to the Pix2pix model, the GauGAN model is much more precise, allowing the generated bitmap to be more easily converted into a vector graph (Pan et al, 2020). The resulting GAN bitmaps are converted back to a 3D model, as shown in Figure 3.…”
Section: Gan Model Training and Vectorized Model Generationmentioning
confidence: 99%